2018
DOI: 10.17556/erziefd.330587
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğrencilerinin Okuma Becerileri Üzerine Bir İnceleme

Abstract: In this study, it was aimed to investigate the relation between middle school students' fluent reading skills and their level of reader self-efficacy and attitude toward reading, using social media; to reveal whether level of fluent reading differentiate according to tex gender. 340 middle school students who were chosen through random sampling method from Yozgat city center participated in the research. The research was carried out with descriptive and relational screening model from quantitative designs. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…Similarly, it is underlined that gender/sex does not affect problem-solving skills in the research carried out by Çilingir (2006), Gültekin (2006), Özkütük et al (2003), Tümkaya and Iflazoğlu (1999). Unlike the previous research, it is pointed out that female student's problem-solving skills are higher than male students in the research of Ferah (2000), Katkat and Mızrak (2003), Serin and Derin (2008) and Yıldırım and colleagues (2011), yet the research of Korkut (2002) and Koray and Azar (2008) male students' problem-solving skills found higher than female students. However, it can be expected that pre-service teachers who participate in physics courses could develop more physics problem-solving abilities compared with other preservice teachers from other programs such as science, elementary, and computer and instructional technology.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Similarly, it is underlined that gender/sex does not affect problem-solving skills in the research carried out by Çilingir (2006), Gültekin (2006), Özkütük et al (2003), Tümkaya and Iflazoğlu (1999). Unlike the previous research, it is pointed out that female student's problem-solving skills are higher than male students in the research of Ferah (2000), Katkat and Mızrak (2003), Serin and Derin (2008) and Yıldırım and colleagues (2011), yet the research of Korkut (2002) and Koray and Azar (2008) male students' problem-solving skills found higher than female students. However, it can be expected that pre-service teachers who participate in physics courses could develop more physics problem-solving abilities compared with other preservice teachers from other programs such as science, elementary, and computer and instructional technology.…”
Section: Discussionmentioning
confidence: 74%
“…Tables 2 and 4 also reveal that pre-service teacher as high school students who graduated from Super High School and Anatolian Teacher Training High School can solve physics problems at a higher level than those of Classical High School. As for the research which was carried out by Korkut (2002), it is concluded that there is no effect of having an education from Super or General high schools on students' problem-solving skills. Since problem-solving is an inquiring task, the students find out the solution pathway to reach course objectives from problem situations or given information (Docktor et al, 2015;Dinica et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Ertok-Atmaca'ya (2006) göre ders kitapları eğitim-öğretim sürecinin nasıl işleyeceği, neler öğretileceği konusunda öğretmenlere yol gösterici bir kaynaktır. Ayrıca ders kitaplarının eğitim-öğretim sürecinin vazgeçilmez en önemli kaynaklarından biri olduğunu söylemek mümkündür (Kayman ve Kaya, 2021). Bu nedenle ders kitaplarının içeriği, teknik ve fiziksel özellikleri oldukça önemlidir.…”
Section: Introductionunclassified